Tooth exposure using closed eruption modification techniques in orthodontic treatment in postgnatoplasty patients - Miftah Dharma Yanthi; Cahya Yustisia Hasan; Bambang Dwirahardjo (MKGK (Majalah Kedokteran Gigi Klinik) (Clinical Dental Journal) UGM, 2017)
Cleft lip, alveolar cleft, and cleft palate are the most common disorder of all congenital abnormalities of the face, with an incidence of 65%. The initial treatment for this patient are labioplasty and palatoplasty that can affect the growth and development of the jaws. The next treatment are alveolar cleft closure and orthodontics treatment that are needed to obtain optimal results. Orthodontics treatment of patient with cleft lip, alveolar cleft, and cleft palate is difficult due to the lack of growth in the vertical and anteroposterior direction, abnormal shape and position of the teeth, impacted and disability of the teeth to erupt spontaneously. Thus, surgical treatment to support the success of orthodontics treatment is needed. Twelve year old female patient with a history of cleft lip, alveolar cleft, and cleft palate was presented. A labioplasty, palatoplasty, and gnatoplasty surgery (alveolar cleft closure procedure) was performed in 2013, when a bone graft from the patients’ iliac bone was placed on the alveolar cleft area. Radiographic examination showed transposition of canine (23) with premolar (24) thus spontaneous eruption was impossible. Surgical intervention of tooth exposure using closed technique modification to move the canine into the expected place was performed. The canine was successfully erupted and moved to its mesial position. This predictable result was found 6 months after surgery